The Determination of Nutritional Habits of Students - Akbulut, Abdullah Kursad (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to determine the nutritional habits of the students studying at Ardahan University School of Physical Education and Sports.  The population of the research was selected by random method, with 51 female students and 86 male students from the Physical Education and Sports Teaching Department (n=30), Sports Management Department (n=107) Methods: In the analysis of the research data, descriptive statistics such as arithmetic mean, frequency, standard deviation, and percentage values ​​are examined. In order to determine whether the parametric analyzes will be performed for this study, it was primarily assessed whether the scale data showed a normal distribution. Results: According to the results obtained, it is observed that the level of the 4th grade students in the sub-dimension of products used other than food is significantly higher than the 1st grade students. Accordingly, it can be claimed that 4th grade students consume products other than food more than 1st grade students. For the food consumption frequency sub-dimension, the levels of the 3rd grade students are found to be higher with a significant difference compared to the 2nd grade students. In the general averages of the eating habits scale, it is observed that the levels of the 3rd year students are higher than the 1st year students with a significant difference. According to the results of the research, for the sub-dimension of products used other than food, it is seen that the levels of the students of the sports management department are significantly higher than the students of the teaching department. Conclusion: In other words, it can be proclaimed that sports management students consume products other than food more than the students of the teaching department. Within the context of the sub-dimensions of the nutrition scale; according to the results of the nutritional habits dimension, it can be detected that the students exhibit a high level of positive behavior for the dimensions of eating habits and the frequency of food consumption, and a low level of behavior in the dimension of products used other than food.